Studying the Possibility of Separation of Primary Nuclei Groups in the Energy Interval 300 TeV – 10 PeV in the TAIGA-HiSCORE Experiment. (February 2019) - Sveshnikova, L; Sh Elshoukrofy, A; Postnikov, E; Korosteleva, E; Motaweh, H
Abstract: We proposed a method of discrimination between light (p+He) and heavy (C+Fe) groups of primary nuclei. It's based on parametric analysis of lateral distribution of Cherenkov light in the atmosphere with approximation by the 'knee-like' fitting function, proposed and studied earlier. Two parameters most sensitive to the depth of shower maximum were revealed and used for analysis of the bulk of experimental data obtained in the TAIGA-HiSCORE experiment in the energy range 300–3000 TeV for various incident angles of particles. It is shown that the method allows estimating the contribution of light and heavy groups of primary nuclei. In the interval 300–3000 TeV we do not see a rapid decrease of the light component flux, as it was seen in the ARGO-YBJ experiment. This result will be refined after a more detailed analysis.